Redefining reproductive rights through a harmonised approach of international human rights law and Islamic law - Zawawi, Majdah (2009)
This paper looks into the way reproductive rights have been defined in light of advances made in the area of assisted reproductive technologies (ART). It discusses the problem that arises in defining reproductive rights in view of giving primacy to individual rights. Hence, the paper proposes that the term may be re-defined by not only emphasising individual rights, but also by looking at arising responsibilities that arises when a person decides to reproduce. In doing so, the paper discusses the position reproductive rights under existing International Human Rights Law whilst also looking at it from the Shari'ah perspective.